PEMBERIAN BIMBINGAN KARIR DENGAN PENGEMBANGAN POTENSI DIRI PESERTA DIDIK - Syufriatullailah; Zahroh As Sakinah; Cucu Atikah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Students are a group of immature individuals trying to discover something and develop their personal potential through various learning processes in the community and at school. So, it is very important for the development of students to work with different parties around them to achieve optimal development. In this case, without any help, the negative environmental impact will be very difficult to control. Therefore, the process of discovering and developing students’ personal potential really needs guidance from parents at home, educators at school, especially educational consultants. In this study, the author’s reason for choosing this title is to provide career guidance in developing students’ potential. Thank you to the author for finding a number of cases both from his experience and from the perspective of some existing phenomena, but there are still many student who do not clearly know their potential and future career. Future or career goals. The research method used is quantitative with descriptive analysis method, research subject include 35 students, data collection techniques uses questionnaires. Data analysis techniques used include validity and reliability testing, normality testing, homogeneity testing, correlation testing, regression testing, and identification. The results of a tested and statistically calculated study show that this hypothesis is accepted. It can be concluded that the relationship between providing career guidance and development of student’s potential is linear because the linear data in skewed from is significant at the level of 1.158 > 0.05.